Student Political Participation in the 2023 Medan State University Elections: (Study at Unimed PPKn Department) - Giry, Taufiq Wijaya; Halking, Halking (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Indonesia is a democratic country. One of the indicators in measuring the level of democracy is political participation. The implementation of political participation in society is in the election of people's representatives. The election process is known as elections. Elections do not only exist in the community, but in the scope of the campus there is also what is known as Pemira. Pemira (General Election) is the biggest democratic party at Medan State University. Just like a country that has a leader as a representative of the people, students also have a high official who acts as a representative of students at both the university and faculty levels. Based on data that suggests that student political participation is low in Pemira 2023, namely 65% of students do not use their voting rights. The purpose of this research is to find out how political participation and what obstacles students experience in Pemira 2023.This type of research is  descriptive research with qualitative research methods. The informants in this study were students in the Civics department, the Pemira committee, and the Vice Dean 3 of FIS. The data used in this research are primary data and secondary data. Data collection techniques using interview techniques, with data collection instruments in the form of interview list sheets, books, journals, diaries, cameras, recording devices and so on. Data analysis used qualitative data analysis through 3 stages, including data reduction, data presentation, and verification/conclusion. The results showed that in Pemira 2023 the level of student political participation was low due to low student curiosity in Pemira and low student interest in becoming contestants in Pemira due to other tasks and student distrust of the organizations offered. The obstacles experienced by students in the 2023 Pemira were related to the low role of the committee in socializing information related to system improvements in the application used for elections, which caused many students to be unable to enter the Pemira application and did not exercise their voting rights.